Guide Bot – система навигации антропоморфных агентов виртуальной реальности - Добронравин, Ю.В; Самарин, Н.С. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
Agents’ navigation and movement in 3D space is a high priority task for the developers of virtual reality. Guide Bot is a professional AI pathfinder solution for game and virtual reality pplications. This paper describes main features of Guide Bot and core ideas behind its design.